Ghana - Mining and Development - Mohan, P.C. (World Bank, Washington, DC, 2012)
The objectives of the project ($9.37 million, 1996-2001) were to (a) enhance the capacity of the mining sector institutions to carry out their functions of encouraging and regulating investments in the mining sector in an environmentally sound manner and (b) support the use of techniques and mechanisms that will improve productivity, financial viability and reduce the environmental impact of small-scale mining operations. It had two components: Strengthening of Mining Sector Institutions, and Assistance to Small-scale Mining Enterprises. The project took into account lessons learned from three previous operations in Ghana which focused on developing the mining sector: the Export Rehabilitation project, the Export Rehabilitation Technical Assistance project, and the Mining Sector Rehabilitation project.